The Effect of a Period of Circuit Resistance Training on Serum Level of Apelin, Vaspin, and Blood Pressure in Elderly Men with Hypertension - Bizhan Hooshmand Moghadam; Shadi Moazami Goudarzi; Amir Rashid Lamir (Tehran University of Medical Sciences, 2024)
Background and Aim: Adipokines imbalance causes pathological effects on this system. Exercise interventions can play an important role in regulating the secretion of adipokines. This study aimed to investigate the effect of 12 weeks of resistance training on the serum level of apelin, vaspin, and blood pressure in elderly men with hypertension. Materials and Methods: In this quasi-experimental study, 24 elderly men with high blood pressure were selected purposefully and based on the inclusion criteria and were randomly assigned to resistance training (N=12) and control (N=12) groups. The participants of the resistance training group performed resistance training for 12 weeks and three days a week. At the beginning and end of the study, blood samples were collected to measure the serum level of apelin and vaspin. Data analysis was performed using SPSS version 24 software with dependent and independent t-tests at a significant level of less than 0.05. Results: After 12 weeks of resistance training, there was a significant decrease in the serum level of apelin (P=0.002), vaspin (P=0.01), systolic blood pressure (P<0.001), and diastolic blood pressure (P<0.001) as compared to the pre-test. In addition, a significant difference was observed between the two experimental and control groups in the serum level of apelin (p=0.001), vaspin (P=0.001), systolic blood pressure (P<0.001), and diastolic blood pressure (P<0.001). Conclusion: It seems 12 weeks of resistance training can improve systolic and diastolic blood pressure and regulate the secretion of adipokines apelin and vaspin in elderly men with high blood pressure.